Strategy Encouraging Participation of New Voters in The 2024 Surabaya City Regional Elections - Moch Rozzaq Febriansyah; Muhammad Agus Muljanto (Jurnal Kebijakan Publik, 2025)
This research focuses on analyzing the strategy of the General Election Commission (KPU) of Surabaya City in encouraging the participation of novice voters in the Regional Head Election (Pilkada). This research uses a qualitative method with a descriptive approach through data collection techniques in the form of semi-structured interviews, observation, and documentation. The results of this study use SWOT analysis which consists of strengths, weaknesses, opportunities, and threats. The results showed: (1) Strength factors owned by the General Election Commission (KPU) of Surabaya City, namely having qualified human resources, the existence of the KPU Goes To School socialization program to encourage the participation of novice voters; (2) Weakness factors, namely the lack of socialization coverage to all schools, the limited space of the Surabaya City KPU due to the code of ethics; (3) Opportunity factors, namely the use of social media to continue to increase awareness of novice voters in the form of electronic media, collaborating with stakeholders to conduct voter education socialization; (4) Threat factors, namely the empty box election so that there are people who hold demonstrations against empty box nominations, negative perspectives from novice voters about empty box nominations, low voter participation in the 2024 Surabaya City Pilkada.